2010
DOI: 10.1021/jp1035103
|View full text |Cite
|
Sign up to set email alerts
|

The Cu Promoter in an Iron−Chromium−Oxide Based Water−Gas Shift Catalyst under Industrial Conditions Studied by in-Situ XAFS

Abstract: The chemical state of the Cu promoter (1 wt %) in a Cu-promoted Cr-stabilized iron oxide based water−gas shift catalyst has been studied by in-situ X-ray absorption fine structure (XAFS) at 380 °C and elevated pressures, which is close to the conditions typically applied in industrial processes. The Cu promoter enhances the activity of the catalyst. In this study, the catalyst has been studied as fresh, after use for 2000 h, and after a further wash with an aqueous solution of ammonia. In all three cases, CuO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 27 publications
4
26
0
Order By: Relevance
“…CO + H 2 O ⇄ CO 2 + H 2 ; ∆H°= −41 kJ mol −1 (1) In industry the WGS reaction is carried out in two stages: the high temperature shift (623-773 K) using Fe 2 O 3 /Cr 2 O 3 /Cu catalyst, reducing the concentration of CO to typically around 2% and the low temperature shift (473-513 K) using CuO/ZnO/Al 2 O 3 catalyst, reducing the concentration of CO to ppm levels (typically <3000 ppm) [2,3]. Recently, from industry [4] and academia [5,6] work is reported to develop chromium-free high temperature shift catalysts because of environmental and health hazards to handle chromium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO + H 2 O ⇄ CO 2 + H 2 ; ∆H°= −41 kJ mol −1 (1) In industry the WGS reaction is carried out in two stages: the high temperature shift (623-773 K) using Fe 2 O 3 /Cr 2 O 3 /Cu catalyst, reducing the concentration of CO to typically around 2% and the low temperature shift (473-513 K) using CuO/ZnO/Al 2 O 3 catalyst, reducing the concentration of CO to ppm levels (typically <3000 ppm) [2,3]. Recently, from industry [4] and academia [5,6] work is reported to develop chromium-free high temperature shift catalysts because of environmental and health hazards to handle chromium.…”
Section: Introductionmentioning
confidence: 99%
“…2) often describes data well in the limited range of process conditions [8,9]. 2 represents the approach to equilibrium, p i the partial pressure of each component, K e is the WGS equilibrium constant and k is the apparent rate constant. However, to have more meaningful representation of the kinetic data, micro-kinetic models based on different WGS mechanisms have also been used [11,12,18,20].…”
Section: Introductionmentioning
confidence: 99%
“…EOR is defined as the fraction of iron that has been reduced from Fe 2 O 3 to either Fe 3 O 4 (in the second column of Table 1) or to metallic iron (in the third and fourth columns of Table 1) as quantified by the integrated hydrogen consumption from the TPR peaks. The listed values have been corrected by subtracting the small amount of hydrogen expected to be consumed by the other reducible catalyst components, CuO to Cu and Cr 6+ to Cr 3+ , which are reported to reduce near the temperature range of the first peak [40][41][42]. Hydrogen consumption increases with La content for the first reduction phase and is approximately the same for the second reduction phase (within the ±5% error for this experiment).…”
Section: Temperature-programmed Reduction and Oxidation (Tpr And Tpo)mentioning
confidence: 51%
“…Two peaks were observed during the reduction of the catalysts with H 2 , in which the first peak corresponds to the reduction of Fe 2 O 3 to Fe 3 O 4 , CuO to Cu and possibly Cr 6+ to Cr 3+ , while the second peak is attributed to the reduction of Fe 3 O 4 to FeO and metallic Fe [40][41][42]. The second peak is much larger than the first peak because it requires 8 times more H 2 to reduce Fe 3 O 4 to Fe than to reduce Fe 2 O 3 to Fe 3 O 4 .…”
Section: Temperature-programmed Reduction and Oxidation (Tpr And Tpo)mentioning
confidence: 99%
“…In industry the WGS reaction is carried out in two stages: the high temperature shift (623-773 K) using Fe 2 O 3 /Cr 2 O 3 /Cu catalyst, reducing the concentration of CO to typically around 2% and the low temperature shift (473-513 K) using CuO/ZnO/Al 2 O 3 catalyst, reducing the concentration of CO to ppm levels (typically < 3000 ppm) [41,42]. Sakurai et al [43] reported Au (3.3-10 wt.%)/TiO 2 P25 as a highly active low temperature WGS better than the commercial low temperature WGS catalyst CuO/ZnO/Al 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%